2003
DOI: 10.1177/000348940311201212
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Visualization of Endolymphatic Hydrops in Guinea Pigs: Magnetic Resonance Imaging Evaluation at 4.7 Tesla

Abstract: In order to find out whether it is possible to visualize experimental endolymphatic hydrops in the cochlea with magnetic resonance imaging (MRI) at 4.7 T, we used 11 guinea pigs. Five normal guinea pigs were used as controls. Early manifestation of endolymphatic hydrops was evaluated in endolymphatic sac (ES)-intact animals (n = 6), and advanced manifestation in ES-damaged animals (n = 5) by means of MRI with gadolinium-diethylenetriaminepentaacetate-bismethylamide (Gd-DTPA-BMA) contrast agent. Hearing was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 10 publications
6
43
0
Order By: Relevance
“…There is potential to use this method to visualize endolymphatic hydrops and the permeability change or rupture of Reissner’s membrane, as has been done in guinea pigs [14]. This can be improved with a better coil structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is potential to use this method to visualize endolymphatic hydrops and the permeability change or rupture of Reissner’s membrane, as has been done in guinea pigs [14]. This can be improved with a better coil structure.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of Gd in the cochlear chambers was monitored in 10-min intervals over a period of 40–90 min following administration. All the parameters were the same as previously reported [14]. The field of view was 3 cm, slice thickness 0.5 mm, centre-centre separation 0.65 mm, acquisition matrix 256 × 256 and reconstruction matrix 512 × 512, recovery time 500 ms and repetition time 693.1 ms. RARE factor was 32, time between refocusing pulses 6.1 ms and phase encoding gradient increment such as to yield an effective echo time of 31.5 ms.…”
Section: Methodsmentioning
confidence: 99%
“…The advantage of a sequence with strong T1-weighting, such as FLASH used in this work and FLAIR (1,2), is that it can be used to study gadolinium concentrations that change between cochlear chambers at different times between injection and imaging (5); the disadvantage is that gadolinium injection is very invasive (7). CISS can obtain high SNR images without gadolinium injection, but suffers from banding artifacts (7) that complicate image interpretation, so is used primarily for obtaining anatomical reference images (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium-enhanced inner ear MRI became a valuable diagnostic tool in inner ear diseases after two milestone studies showed that the cochlear scalae were distinguishable, and that the experimental endolymphatichy drops was visible in vivo in 4.7 T MRI after intravenous injection of Gadolinium Diethylenetriaminepentaacetic Acid Bismethylamide (Gd-DTPA-BMA) in guinea pigs [1][2][3]. In the studies, high-dose Gadolinium chelate (GdC) was applied intravenously to induce enough distribution in the inner ear because GdC has poor transport efficacy across the blood-perilymph barrier [4][5][6].…”
Section: Introductionmentioning
confidence: 99%